Application of Nano‐Sized RDX in CMDB Propellant with High Solid Content. Issue 1 (26th July 2021) - Yu, Haomiao; Sun, Sensen; Gao, Jianbing; Jin, Xiaoxun; Liu, Jie; Li, Fengsheng
Abstract: Compared to the ordinary RDX, nano‐sized RDX has many more excellent properties. Therefore two kinds of CMDB propellant were prepared for comparison. One is the normal CMDB propellant called M‐CMDB propellant, the other is N‐CMDB propellant which adds nano‐sized RDX to CMDB propellant. The morphology characterization, tensile properties, sensitivity, and combustion performance of the propellants were investigated, the results for N‐CMDB propellant were compared with that for the normal one. It has been found that the interface of N‐CMDB propellant showed no stratification and fewer overall defects than the normal one. The value of σm and ϵm for N‐CMDB propellant are increased by 32.6 % and 25.2 % at 323.15 K, respectively. At 293.15 K, the σm and ϵm values of N‐CMDB propellant also increased by 25.4 % and 46.9 % and increased by 17.5 % and 23.7 %, respectively, at 233.15 K. The friction and impact sensitivities of N‐CMDB propellant are decreased by 51.3 % and 50.4 %, respectively. The TG/DSC study indicated that, compared with M‐CMDB propellant, the thermal decomposition peak temperature of N‐CMDB propellant is advanced, and the apparent activation energy is reduced by about 6.0 % to 144.3 kJ ⋅ mol −1 . Combustion performance measurements were carried out. It was observed that nano‐sized RDX is a good burning rate enhancer, because of the burning rate coefficient value of N‐CMDB propellant is relatedly increased by 36.9 %. Besides, the pressure exponent of N‐CMDB propellant is relatively decreased by 21.6 %. All the results indicate that the application of nano‐sized RDX will help to improve the comprehensive performance of CMDB propellant. Abstract :